Hands-on design patterns and best practices with Julia : proven solutions to common problems in software design for Julia 1. x - Kwong, Tom (Packt Publishing, 2020)
Design patterns are fundamental techniques for developing reusable and maintainable code. This book presents many practical design patterns and related techniques for developing Julia applications. By the end of the book, you will be comfortable with implementing design patterns to create robust, reusable, and easily maintainable applications.